The Encapsulation of Anthocyanins from Berry-Type Fruits. Trends in Foods - Paz Robert; Carolina Fredes (Molecules, 2015)
During the last decade, many berry-type fruits have been recognised as good sources of anthocyanins. Nevertheless, the use of anthocyanins in the development of food colourants and healthy and/or functional ingredients has been limited because of their low stability under given environmental conditions and interaction with other compounds in the food matrix. This review compiles information about the encapsulation of anthocyanins from twelve different berry-type fruit species as a technology for improving the stability and/or bioavailability of anthocyanins. Encapsulation by spray drying has been the primary method used to encapsulate anthocyanins, and some studies attempt to keep anthocyanin microparticles stable during storage. Nevertheless, more studies are needed to determine the stability of anthocyanin microparticles in food matrices over the product shelf life in the development of food colourants. Studies about encapsulated anthocyanins in simulated gastrointestinal models have primarily been conducted on the release of anthocyanins from microparticles to evaluate their bioavailability. However, adding anthocyanin microparticles to a food vehicle must guarantee the health properties attributed to the specific anthocyanins present in berry-type fruits.